2013
DOI: 10.1007/s12155-012-9290-3
|View full text |Cite
|
Sign up to set email alerts
|

Water Use Efficiency by Switchgrass Compared to a Native Grass or a Native Grass Alfalfa Mixture

Abstract: Perennial grass systems are being evaluated as a bioenergy feedstock in the northern Great Plains. Inter-annual and inter-seasonal precipitation variation in this region will require efficient water use to maintain sufficient yield production to support a mature bioenergy industry. Objectives were to evaluate the impact of a May-June (early season) and a July-August (late season) drought on the water use efficiency (WUE), amount of water used, and biomass production in monocultures of switchgrass (Panicum virg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
2
13
0
4
Order By: Relevance
“…Á. Löve] pasture was reported by Hendrickson et al. (2013) in North Dakota, where rainfall was normal during May–June and 50% of normal during July–August. One of the reasons that an alfalfa–grass mixture showed higher WUE over grass‐only stands was that alfalfa can grow over a longer season than grasses, especially in the latter part of the growing season (Sleugh et al., 2000).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Á. Löve] pasture was reported by Hendrickson et al. (2013) in North Dakota, where rainfall was normal during May–June and 50% of normal during July–August. One of the reasons that an alfalfa–grass mixture showed higher WUE over grass‐only stands was that alfalfa can grow over a longer season than grasses, especially in the latter part of the growing season (Sleugh et al., 2000).…”
Section: Resultsmentioning
confidence: 87%
“…Hendrickson, Schmer, and Sanderson (2013) suggested that an improvement in transpiration use efficiency can increase the WUE of crops either by enhancing biomass production or by reducing water consumption. Modern cultivars are believed to have higher transpiration use efficiency than traditional cultivars through a series of genetic improvements (Turner, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…WUE values of switchgrass in Tennessee and Oklahoma were 3.5 to 6.3 mg CH 2 O per g of water transpired [37]. Sunburst switchgrass had WUE values ranging from 5.6 to 7.4 mg dry weight per gram of water used [48]. WUE of switchgrass grown in a grassland in Nebraska with little bluestem was 5 mg dry weight per gram of water transpired during the boot or heading stages and dropped to 1 mg g −1 during ripening stage [40].…”
Section: Calculating Wue With the Almanac Modelmentioning
confidence: 99%
“…Según Hendrickson et al, (2013) una manera de mejorar la EUA sería lograr que la pastura genere más biomasa con la misma cantidad de agua o utilizar menos agua para producir la misma biomasa.…”
Section: Resultados Y Discusiónunclassified